Influence of different peritoneal dialysis fluids on the in vitro activity of fosfomycin against Escherichia coli, Staphylococcus aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa - Kussmann, Manuel (Eur J Clin Microbiol Infect Dis, 2018)
Peritonitis is still the main infectious complication among patients on peritoneal dialysis. For treatment of peritoneal dialysis-related peritonitis, the intraperitoneal administration of antibiotics admixed to peritoneal dialysis fluids (PDFs) should be preferred. However, the influence of diverse PDFs on the activity of frequently used antibiotics has been investigated insufficiently. Thus, the present study set out to investigate the in vitro activity of fosfomycin against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus epidermidis, and Staphylococcus aureus in commercially available PDFs. Time-kill curves in four different PDFs (Dianeal®, Extraneal®, Nutrineal®, and Physioneal®) were performed over 24 h with two different concentrations of fosfomycin (150 and 400 mg/L) and without antibiotics as control. Cation-adjusted Mueller Hinton broth (CA-MHB) was used as a comparator solution. In blank PDFs, bacterial growth of each organism evaluated was reduced when compared to CA-MHB. For S. aureus in blank Physioneal®, a reduction under the limit of detection was observed within 24 h. The activity of fosfomycin was reduced in all PDFs when compared to CA-MHB except for P. aeruginosa in Nutrineal® where the activity of fosfomycin was increased when investigated at 400 mg/L. Against E.coli, bactericidal activity was demonstrated in Extraneal®, Nutrineal®, and Physioneal®. Fosfomycin resistance (MIC > 1024 mg/L) was observed for P. aeruginosa in CA-MHB at both concentrations and in Nutrineal® at 150 mg/L. Fosfomycin is active in PDFs particularly against the frequently isolated enterobacterium E. coli. The choice of the respective PDF considerably influences the microbiological outcome in vitro. Further studies are warranted to investigate the clinical relevance of these findings.